THE APPLICATION OF VIBRATION SYSTEM on DRYER MACHINE to DRY RDF AND AGRICULTURAL PRODUCTS BY USING GREEN INCINERATOR - La Ode Mohammad Firman; Dwi R; Budhi M.S. (Universitas Sultan Ageng Tirtayasa, 2019)
Increasing heat and vapor transfer between air and product to be dried is an important issue in drying of Refuse Derived Fuel (RDF) and agricultural products. Generally, manual mixing is used in order to increase the contact area between air and product to be dried. The applications of vibration system on dryer machine can be used to dry RDF and agricultural products. Even if the use of dryer machines has been widely used to dry RDF and agricultural products with avoiding the heat loss needs to be verified. The observations shown that the using of vibration system for moving RDF and agricultural products were on the shelf could not be moved optimally. The previous study found that the spring load on dryer machine was too large and most of the surface of RDF and agricultural products were on the shelf could not get hot air flow. That’s why the spring used as pedestal of shelves would be broken fast and on a specific moment RDF and agricultural products must be taken out of the drying chamber to be manually moved. To solve the problems and to develop the results of previous study, then it needs to do the study about analysis, simulation and experimental of vibration. In this study, vibration was analyzed to having an insight on suitable condition of the dryer machine for use in drying RDF and agricultural products. Beside that the study only uses an unbalance mass and it does not use a piston engine, so spring load would be smaller. The objectives of the study is to perform analysis, simulation and experimental of vibration in order that the RDF and agricultural products are on the each shelf can be dried fast and moved optimally. The study use observation, literature study, analysis, simulation and experimental methods and cashew nuts as the material tested on the each shelf. The study results show that the condition of vibration approached resonance cause cashew nuts placed on the each shelf could be moved optimally, therefore the surface of RDF and agricultural products were on the shelf could get hot air flow. The final moisture content of vibrated samples was lower than the samples without vibration